Pemeriksaan dan Penyuluhan Kesehatan Diabetes Melitus pada Lansia - Harwati, Andriati Reny; Rahayu, Sri (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Diabetes is a chronic disease characterized by higher than normal blood sugar levels in the body. This disease is common in the elderly. Given that diabetes is a dangerous disease, treatment is needed to overcome this problem. One of the preventive efforts that can be done is by conducting screening through blood sugar level checks, as well as providing health information about diabetes. This activity aims to determine the blood sugar levels of the elderly so that diabetes can be detected early and increase the elderly's understanding of diabetes mellitus. The method used is blood sugar examination and health education. It is known that the elderly with random blood sugar levels ≥ 200 mg / dl are 19 people (30%). Evaluation of health education is carried out through questions and answers, most participants can answer questions well related to diabetes. It is necessary to carry out blood sugar examination activities and diabetes health education periodically so that it is hoped that the elderly can be motivated to carry out positive health behaviors in efforts to prevent or treat diabetes.